Foraging and Drifting Patterns of the Highly Eusocial Neotropical Stingless Bee Melipona fasciculata Assessed by Radio-Frequency Identification Tags - Oliveira, Ricardo Caliari; Contrera, Felipe Andrés León; Arruda, Helder; Jaffé, Rodolfo; Costa, Luciano; Pessin, Gustavo; Venturieri, Giorgio Cristino; de Souza, Paulo; Imperatriz-Fonseca, Vera Lúcia (Frontiers in Ecology and Evolution, 2021)
Bees play a key role in ecosystem services as the main pollinators of numerous flowering plants. Studying factors influencing their foraging behaviour is relevant not only to understand their biology, but also how populations might respond to changes in their habitat and to the climate. Here, we used radio-frequency identification tags to monitor the foraging behaviour of the neotropical stingless bee Melipona fasciculata with special interest in drifting patterns i.e., when a forager drifts into a foreign nest. In addition, we collected meteorological data to study how abiotic factors affect bees’ activity and behaviour. Our results show that only 35 % of bees never drifted to another hive nearby, and that factors such as temperature, humidity and solar irradiation affected the bees drifting rates and/or foraging activity. Moreover, we tested whether drifting levels would decrease after marking the nest entrances with different patterns. However, contrary to our predictions, there was an increase in the proportion of drifting, which could indicate factors other than orientation mistakes playing a role in this behaviour. Overall, our results demonstrate how managed bee populations are affected by both nearby hives and climate factors, offering insights on their biology and potential commercial application as crop pollinators.